Top‐down self‐regulation processes as determinants of oral hygiene self‐care behaviour: A systematic scoping review. Issue 4 (9th April 2022) - Rogers, Adam A.; Willumsen, Tiril; Strømme, Hilde; Johnsen, Jan‐Are K.
Abstract: Objectives: Understanding the psychological mechanisms that moderate oral hygiene self‐care behavior is anticipated to benefit efforts to change such behavior. Top‐down self‐regulatory (TSR) processes represent one group of relatively unexplored, yet potentially influential, moderating factors. This systematic scoping review aims to explore whether there is evidence that TSR processes moderate oral hygiene self‐care engagement within the current literature. Methods: CINAHL, The Cochrane Library, Embase, MEDLINE, PsycINFO, Scopus, and Web of Science databases were searched up to April 2020 for articles that compared measures of TSR processes (such as self‐monitoring, inhibitory control, and task switching) to oral hygiene self‐care behavior, or tested interventions that aimed to change or support TSR processes. Results: The search returned 6626 articles, with 25 included in the final sample. Weak evidence supported both the role of TSR processes as moderators of interdental cleaning and the value of interventions targeting self‐monitoring of interdental cleaning behavior. Overall, methodological limitations rendered the findings somewhat inconclusive, with an absence of objective assessments of TSR capacity, and little focus on TSR processes as moderators of intervention effects. Conclusions: The inconclusive, but reasonably promising, findings point to the value of continuing to apply TSR processes within studies of oral hygiene behavior. Exploring why interdental cleaning appears more reliant on TSR processes than toothbrushing, employing objective neuropsychological assessment, and measuring TSR constructs within interventions targeting TSR processes, are encouraged. As a scoping review, the study hopes to generate interest and serve as a starting point for further investigation.